Improvement in health-related quality of life with Botulinum toxin A injection in acquired superior oblique palsy - Chen, Chonglin; Xu, Meiping; Yu, Huanyun; Li, Yipao; Yu, Xinping (Frontiers in Medicine, 2023)
Purpose This study aimed to investigate the outcomes of Botulinum toxin A (BTA) injection into the inferior oblique (IO) muscle for the management of unilateral acute acquired superior oblique palsy (SOP) and to evaluate changes in health-related quality of life post-injection using the Adult Strabismus-20 (AS-20) questionnaire. Methods A prospective cohort study was performed in patients with unilateral acute acquired SOP who received BTA injections. Four units of BTA were injected into the ipsilateral IO muscle. Ocular examinations were performed pre-and post-injection, including alignment, ocular movement, and cyclotorsion deviation. The patients’ AS-20 questionnaire scores were analyzed. Results A total of 21 patients with acute acquired SOP were included. The initial median vertical deviation was 5 PD (range 1–16), which was improved to 0 PD (range 0–10) at both 1 and 6 months post-injection (p < 0.001 and p < 0.001, respectively). The median torsional deviation was 7° (range 2–18) at baseline and resolved to 0 degrees (range −3–5) at the 1-month and 0° (range −2–7) at the 6-month follow-up (p < 0.001 and p < 0.001, respectively). There were significant increases in the overall score (OAS), psychosocial subscale score (PSS), and functional subscale score (FSS) from baseline values at both the 1-month (p < 0.001, p < 0.001, and p = 0.001, respectively) and 6-month follow-up (all p < 0.001). Conclusion Injecting BTA into the ipsilateral IO muscle successfully resolved vertical and torsional deviations and significantly improved quality-of-life scores. Our findings show that BTA treatment, as an early treatment for acute acquired SOP, can help patients by significantly improving their quality of life.